(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
Arc welding is the most commonly used metal joining process and its broad range of applications from large structural fabrications such as bridges to delicate satellite and aerospace components. Welding Residual Stress (WRS) and cracks developed during welding, reduce the quality of welds. Aerospace structures are normally fabricated using thin metal sheets to reduce mass and are always susceptible to buckling. Many researchers have published WRS numerical models and experimental validations, but the impact of WRS on the buckling of thin low carbon steel plates is yet to be studied. The main objective of this study is to analyse the influence of external compressive load and tendon force generated by welding residual stress on buckling strength of the TIG welded low-carbon steel plates. Linear buckling of welded plates under the combined effect of external compressive load and WRS generated due to various weld lengths were numerically modelled and its critical buckling loads are computed. The numerical simulation findings show that the critical buckling strength decreases by 80% when the weld length to plate width ratio (w/wl) is equal to unity and it reduces to minimum when the w/wl ratio is 0.5. After w/wl ratio is 0.5, buckling strength increases and this behavior is caused by the stress field interaction that arises from both the applied axial compressive load and the WRS on the plate.